Urbanisation In India: Causes and Problems: Exploring the impacts and challenges of urbanization in India (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Urbanisation is theprocess of rural migration to urban areas. According to a survey by UN by 2030,40.76% of the country’s population will reside in urban areas. Almost all areasin the cities are developed and there are a lot of employment opportunities,modern and high standard of living but there are a lot of problems due to Urbanisationlike slums, unhygienic conditions, overcrowding, crimes, life stylemodification etc. Girardet in 1996 explained that the impact of cities can beseen both locally and globally in the form of air pollution, sewerage, waterpollution, overcoming etc. The present paper is focused on various causes andproblems of Urbanisation in India.